Explaining the role of job stress and ego empowerment in improving audit quality - Nasim Nasirpour; Mohammad Mehdi Abbasian (Shahid Beheshti University of Medical Sciences, 2021)
Introduction: Ego functions include communication with reality, regulation and control of instinctual forces, thematic relations, thought processing, defensive functions, combined functions and judgment.  The purpose of this study was to investigate the relationship between audit quality with job stress and ego empowerment. Method: This was a cross sectional study conducted on the auditors of the auditing organization and independent auditing companies, which included at least 3 auditors in 2019. finally, 815 people create the total statistical population of this research. Audit quality questionnaire, Job Stress Questionnaire, and Ego Strength Psychological Questionnaire were used to collect data. Results: Total number of 399 auditors with mean age of 31.7± 5.6 years (159 female and 240 male subjects) were included in our study. Results showed that job stress and ego empowerment can predict audit quality.  ego empowerment can predict audit quality. the effect of "job stress" on "audit quality" was confirmed as the null hypothesis, by a p-value of 0.465 (t0.95 = 1.96); so, significance of the effect of "job stress" on "audit quality" can be accepted at the level of type l error (0.05) in this model. job stress can predict the quality of auditing. Effect of "ego empowerment" on "audit quality" was confirmed by statistic P-value of 0.174 (t0.95 = 1.96), rejecting H1 hypothesis; so, ego empowerment can predict the quality of auditing.  Conclusion: The results showed that job stress and ego empowerment can predict audit quality.